Agglomeration and job matching among college graduates - Jaison R. Abel; Richard Deitz (Federal Reserve Bank of New York, 2012)
We study one potential source of urban agglomeration economies: better job matching. Focusing on college graduates, we construct two direct measures of job matching based on how well an individual's job corresponds to his or her college education. Consistent with matching-based theories of urban agglomeration, we find evidence that larger and thicker local labor markets help college graduates find better jobs by increasing both the likelihood and quality of a match. We then assess the extent to which better job matching of college-educated workers increases individual-level wages and thereby contributes to the urban wage premium. While we find that college graduates with better job matches do indeed earn higher wages on average, the contribution of such job matching to aggregate urban productivity appears to be relatively modest.
Keywords: I21; J24; J31; R23; 330; agglomeration; labor market matching; productivity; underemployment; urban wage premium